Differentiation in selection of dicots and grasses by the leaf-cutter Ants Atta capiguara, Atta laevigata and Atta sexdens rubropilosa - Nagamoto, Nilson S. [UNESP]; Carlos, Amanda A. [UNESP]; Moreira, Sinara M. [UNESP]; Verza, Sandra S. [UNESP]; Hirose, Gustavo L. [UNESP]; Forti, Luiz C. [UNESP] (My University, 2009)
Besides foraging for grasses, the so-called grass-cutter ants, such as Atta capiguara (Hym., Formicidae, Attini), have shown, in the laboratory, a high preference for dicots including Acalypha spp. This preference has also been observed in Atta laevigata, a dicot- and grass-cutter species. The present work ascertained whether differences exist in the selection of grasses and dicots by Atta capiguara, Atta laevigata and the dicot cutter Atta sexdens rubropilosa, during foraging. The carrying of leaf discs from two dicots {Acalypha wilkesi-ana and Psidium guajava) and two grasses (Hyparrhenia rufa and Paspalum notatum) was evaluated. A. wilkesiana was the most attractive to all the ants, followed by H. rufa and P. notatum to A. capiguara, P. guajava to A. sexdens rubropilosa and H, rufa to A. laevigata. Differentiation was demonstrated in carrying preference for grasses and dicots, among these ant species, without interference of factors such as leaf hardness or the availability and architecture of plants. It became evident that A. laevigata does not have a clear preference between dicots or grasses, which is different from A. capiguara. It was deduced that dicotyledonous leaf-cutter ants such as A. sexdens rubropilosa do not substantially forage grasses since they are not adapted to overcome the greater resistance of grasses to cutting and due to their innate tendency to not prefer grasses. Foryf capiguara there appears to be no obstacle, in the field, to foraging highly attractive dicots as found therein.
Keywords: Atta; Attini; Dicotyledons; Grass-cutter ant; Grasses; Substrate selection